1993
DOI: 10.1111/j.1476-5381.1993.tb13832.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular actions of purines in the foetal circulation of the human placenta

Abstract: 1 The vasoactive effects of adenosine triphosphate (ATP), adenosine and other purines in the foetal circulation of the human placenta were examined. Single lobules of the placenta were bilaterally perfused in vitro with Krebs buffer (maternal and foetal sides 5 ml min' each, 95% 02:5% CO2, 37°C). Changes in foetal vascular tone were assessed by recording perfusion pressure during constant infusion of each purine. To allow recording of the vasodilator effects, submaximal vasoconstriction was induced by concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…These discrepancies may be related to differences in the source of endothelial cells studied, the length of exposure to adenosine (1 h vs. 2 min), the culture media used (RPMI 1640 vs. M199) or the experimental conditions for measuring NO production. The effects of ATP, adenosine and other purines in the fetal circulation of the human placenta have recently been examined (Read, Boura & Walters, 1993 …”
Section: Resultsmentioning
confidence: 99%
“…These discrepancies may be related to differences in the source of endothelial cells studied, the length of exposure to adenosine (1 h vs. 2 min), the culture media used (RPMI 1640 vs. M199) or the experimental conditions for measuring NO production. The effects of ATP, adenosine and other purines in the fetal circulation of the human placenta have recently been examined (Read, Boura & Walters, 1993 …”
Section: Resultsmentioning
confidence: 99%
“…ATP contracts human placental vascular smooth muscle via P2X receptors; UTP mediates weak vasoconstriction via P2Y 2 (or P2Y 4 ) receptors on smooth muscle; ADP, ATP, and UTP dilate placental vessels, likely via endothelial P2Y 1 and P2Y 2 receptors, and involve release of NO (see Read et al, 1993;Ralevic et al, 1997;Buvinic et al, 2006). Interestingly, contractile responses to ATP and a,b-meATP were sustained in human perfused placental cotyledons and human placental chorionic surface arteries (Dobronyi et al, 1997;Ralevic et al, 1997) in contrast with the rapidly desensitizing responses observed to a,b-meATP via P2X 1 receptors in most other blood vessels.…”
Section: N Human Umbilical and Placental Vesselsmentioning
confidence: 99%
“…ATP, α,β-meATP and β,γ-methylene ATP constricted the perfused human placental cotyledon via P2X receptors, but vasodilation via P2Y receptor-mediated NO release from endothelial cells was also demonstrated [94,336]. ATP increased Ca 2+ uptake by microvillous boarder vesicles formed from term human placental syncytiotrophoblasts [312].…”
Section: Placentamentioning
confidence: 99%